PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP ENVIROMENTAL DISCLOSURE - Bunga Widia Paramitha; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
This study analyze the enviromental disclosure in Indonesia with an annual report reviewing every company that has been listed on BEI . This study examines the influence of the characteristics of the firm as measured by the variable firm size , profitability , leverage and firm size . As for enviromental variables were measured using a weighted disclosure index scores Environmental Reporting ( IER ) . In this study use the control variable composition of the board of commissioners . The sample population by using purposive sampling method with multiple criteria . So there are 101 manufacturing companies that made the object of research . The results showed that there are two variables that are significant to the disclosure enviromental firm size and leverage , while profitability and firm age variables did not significantly influence the enviromental disclosure .